2021
DOI: 10.1111/epi.17158
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of deep brain stimulation compared with vagus nerve stimulation and usual care for patients with refractory epilepsy: A lifetime decision analytic model

Abstract: Objectives: This study was undertaken to estimate the cost-effectiveness of deep brain stimulation (DBS) compared with vagus nerve stimulation (VNS) and care as usual (CAU) for adult patients with refractory epilepsy from a health care perspective using a lifetime decision analytic model. Methods:A Markov decision analytic model was constructed to estimate the lifetime cost-effectiveness of DBS compared with VNS and CAU. Transition probabilities were estimated from a randomized controlled trial, and assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…25 Sensitivity analyses were performed by all studies to determine the confidence of their conclusions. The base case probabilistic sensitivity analysis, when performed, showed that the probability of the results being cost-effective were between 84% 27 and 99.7% 28 for epilepsy surgery and between 1% 26 and 99.9% 25 for neurostimulator treatments. Most models were found to be robust (i.e., sensitivity analysis did not alter the conclusions of cost-effectiveness), and the results were only sensitive to extreme variations in input values, beyond the range of uncertainty.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25 Sensitivity analyses were performed by all studies to determine the confidence of their conclusions. The base case probabilistic sensitivity analysis, when performed, showed that the probability of the results being cost-effective were between 84% 27 and 99.7% 28 for epilepsy surgery and between 1% 26 and 99.9% 25 for neurostimulator treatments. Most models were found to be robust (i.e., sensitivity analysis did not alter the conclusions of cost-effectiveness), and the results were only sensitive to extreme variations in input values, beyond the range of uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…Study Selection, Characteristics, and Quality Ten articles met study eligibility criteria and were included in the final analysis. [22][23][24][25][26][27][28][29][30][31] Study selection workflow is depicted in Figure 1. Year of publication ranged between 1995 and 2022, and study countries/regions included the United States, [22][23][24][25] the EU, 26,28,29 Thailand, 27 England, 30 and Canada.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations